Entrepreneurial leap : do you have what it takes to become an entrepreneur? - Wickman, Gino (Tantor Media, Inc., 2023)
You've thought about starting your own business ... but how can you decide if you should really take the leap? You need answers, not bullshit. This book has them. Entrepreneurial Leap, Updated and Expanded Edition is an easy-to-use guide that will help you decide if entrepreneurship is right for you-because success as an entrepreneur depends on far more than just a great idea and a generous helping of luck. In this three-part book, Gino Wickman, bestselling author of Traction, reveals the six essential traits that every entrepreneur needs in order to succeed, based on real-world startups. If these traits ring true for you, you'll get a glimpse of what your life would look like as an entrepreneur. What's more, Wickman will help you determine what type of business best suits your unique skill set and provide a detailed roadmap that will accelerate your path to startup success. Packed with real-life stories and practical advice, Entrepreneurial Leap, Updated and Expanded Edition is a simple how-to manual for BIG results. Should you take the leap toward entrepreneurship? Find out today and let tomorrow be the first step in your new journey, whatever shape it may take.